Adults' self-reported barriers and enablers to riding a bike for transport: a systematic review. Issue 3 (4th May 2023) - Pearson, Lauren; Berkovic, Danielle; Reeder, Sandy; Gabbe, Belinda; Beck, Ben
ABSTRACT: Riding a bike for transport purposes is an effective way to improve population and environmental health. Despite this, participation levels in many countries are low. Identifying the barriers and enablers to riding a bike for transport is essential to developing interventions that encourage bike riding. In this mixed-methods systematic review, we aimed to identify the perceived barriers and enablers to adults riding a bike for transport in Organisation for Economic Development (OECD) countries. A systematic database search was conducted to identify relevant peer-reviewed and grey literature. Fourty-five papers/reports met eligibility criteria. There were 34 barriers and 21 enablers identified. The leading barriers related to riding on the road alongside motor vehicles. Other factors identified included the provision and quality of cycling infrastructure, personal factors such as physical fitness, attitudinal factors such as community perceptions of cyclists, and environmental factors. While this review highlights the complexity of factors that influence the uptake of riding a bike for transport, many of the leading factors could be overcome through the provision of high-quality protected infrastructure for bike riders. Other interventions to address other known barriers and enablers are needed to increase the uptake of bike riding.